KARAKTERISTIK PENGERINGAN TEPUNG BERAS MENGGUNAKAN ALAT PENGERING TIPE RAK - Rita Khatir; Ratna Ratna; Wardani Wardani (Universitas Syiah Kuala, 2011)
The study aims to enhance the quality and quantity of rice flour in drying process, especially when it is compared to the conventional sun drying. The rice flour was dried for 2 hours at different thickness of 1 and 1.5 cm. The temperatures were measured at several points of the dryer’s tray that is consisted of 4 layers, which was counted from the lowest layer as the first level. The samples were weighed in a small box which was put in the near border of the tray (box A) and in the centre of the tray (box B) for each layer. All measurements were done at interval of 15 minutes. Results showed that the temperature for drying the rice flour at depth 1.5 cm was 66 °C, which was higher than that of drying the rice flour at depth 1 cm (60.5 °C). In consequence, the relative humidity in the drying room at depth 1.5 cm was 35 %, which was lower than that of at depth 1 cm (61.8 %). However, the drying rate at depth 1.5 cm was lower than the drying rate at depth 1 cm. In addition, the distance of tray to the heater was also found to cause the low drying rate.